Root Causes and Safety Challenges of Fatal Construction Accidents in Vietnam - Pham, Xuan Anh; Le, Van Tuan; Nguyen, Quoc Toan; Nguyen, Thi My Hanh (International Journal of Sustainable Construction Engineering and Technology, 2024)
Construction safety is gaining recognition as a keystone of the construction process. The increase in both insurance costs and workers’ compensation makes it necessary to eliminate worksite accidents. This study examines fatal construction accidents in Vietnam from 2014 to 2022, analyzing 440 cases reported by the Ministry of Labor-Invalids-Social Affairs. Findings highlight three predominant types of fatal accidents: falls from height (60.4%), electric shocks (38.5%), and being caught in/between objects (1.1%). Contributing factors include hazardous methods or procedures (34.1%), inadequate support and guards (26.4%), and poor housekeeping (11.0%). Unsafe actions such as failure to use personal protective equipment (18.7%) and disregarding known safety procedures (16.5%) were also significant contributors. The research identifies root causes using the Accident Root Cause Tracing Model (ARCTM), emphasizing the interplay between unsafe conditions and decisions to proceed despite recognizing hazards. Key problems behind accidents include inadequate worker training (53.8%) and insufficient safety management procedures (35.2%). Recommendations focus on enhancing safety training programs, stricter enforcement of safety regulations, and improved on-site safety management practices. The study provides critical insights into reducing fatal accidents in Vietnam’s construction industry and highlights the urgent need for systemic reforms.